S13 Extracellular vesicle miRNA: a mechanism for chronic airway inflammation and macrophage dysfunction in COPD. (December 2018) - Burke, H; Freeman, A; Ostridge, K; Watson, AS; Spalluto, C; Staples, KJ; Wilkinson, TMA
Abstract : Rationale: COPD is characterised by chronic airway inflammation and defective innate immunity, defined in part by airway epithelial cell (AEC) damage and alveolar macrophage dysfunction. The precise mechanisms underlying this interaction are unknown. However, both cell types release extracellular vesicles (EVs) containing microRNA (miRNA) which mediate post-transcriptional regulation of gene expression in target cells. We hypothesise that damaged AECs release EVs with dysregulated miRNA content, altering gene expression in recipient alveolar macrophages, resulting in a pro-inflammatory phenotype with impaired phagocytosis and activation of inflammatory cytokines. We sought to identify differentially expressed EV miRNAs from bronchoalveolar lavage fluid (BALF) in COPD, determine their phenotypic effects and identify key mechanistic regulators that may represent novel therapeutic targets. Methods: EVs were isolated from BALF by size exclusion chromatography from 14 healthy ex-smokers and 17 age-matched mild to moderate COPD patients with a mean FEV1 of 79.9% predicted (SD 13.9%). EV miRNA was sequenced using the Illumina NextSeq500. Raw data was de-multiplexed, trimmed and aligned to hg19. Negative binomial generalised linear models were used to identify differentially expressed miRNAs between COPD and healthy ex-smokers. Targets were validated using RT-qPCR. Results: An average of 2.8 million reads were obtained for each sample and the average genome mapping rate was 54.5%. 54 miRNAs were significantly differentially expressed between COPD and healthy ex-smokers with a FDR<0.05. Five had a fold change of >2, with two upregulated and three downregulated in COPD. Network-based analysis identified these miRNA targeted genes central to pro-inflammatory (TNFα, NF-kβ, and MAPK signalling) and apoptotic pathways. These targets and the phenotypic effects of these dysregulated miRNAs are being investigated using primary ex-vivo co-culture models and in vitro analysis of macrophage function from the same cohort. Conclusion: This work suggests a novel interaction between AECs and alveolar macrophages via delivery of differentially expressed miRNA packaged in EVs. This may provide new insights into the cause of persistent inflammation and macrophage dysfunction in COPD and could identify future targets for disease modifying therapies.